A pragmatic investigation of the translation of swearwords in Arabic-English film subtitling - Sabtan, Yasser Muhammad Naguib (Penerbit Universiti Kebangsaan Malaysia, 2022)
Subtitling, which is a main type of Audiovisual translation (AVT), has only recently received considerable interest in the field of translation studies. As far as the Arabic language is concerned, most studies have been conducted to discuss several problems in subtitling English multimedia material including films into Arabic by amateur or professional subtitlers, while few studies have been carried out to investigate translation problems in subtitling Arabic films into English, especially the problem of translating Arabic swearwords on screen. Swearwords are culturally laden expressions and therefore pose a challenge to film subtitlers who deal with a variety of such expressions in different contexts. In an endeavour to address this gap in that area of AVT, this study attempts to investigate one of the culture-specific problems in Arabic-English film subtitling, namely swearwords. To achieve this goal, a corpus consisting of three Arabic films subtitled into English on an Egyptian TV channel was collected to investigate the translation of these culture-bound expressions. The analysis of the data was carried out utilising Baker’s model of pragmatic equivalence. In this framework, the study sheds light on the strategies used by subtitlers to render the swearwords in Arabic films into English on the TV screen. The results of the analysis show that source language (SL) swearwords are either toned down using euphemistic expressions or completely omitted in the target language (TL) due to ideological and cultural considerations. Moreover, the study reveals that while some SL swearwords are pragmatically translated into their equivalents in the TL, some others do not have the same pragmatic equivalents.